DETERMINAÇÃO DA MICROFLORA DO TRATO GASTRINTESTINAL DE AVESTRUZES (STRUTHIO CAMELUS) CRIADOS NA REGIÃO NOROESTE DO ESTADO DE SÃO PAULO, SUBMETIDAS À NECRÓPSIA - Marinho, M. [UNESP]; Meireles, M.v. [UNESP]; Souza, A.v.g. [UNESP] (Instituto Biológico, 2024)
The raising of ostriches (Struthio camelus) has been implanted in Brazil as a lucrative alternative in the Brazilian livestock, attracting the interest of new farmers. The knowledge of the aerobic and anaerobic gastrointestinal microflora of these birds, besides contributing to their health, would help in the identification of pathogenic microorganisms that also infect the human being and other animals. The present study was aimed to identify of the aerobioc and anaerobioc microorganisms that compose the gastrointestinal microbiota of ostriches submitted to necropsy in the Avian Pathology Service, Medicine Veterinary Course, UNESP, Campus of Araçatuba. Out of 30 birds necropsied, from both sexes and with age varying between 1 day to 3 years of age, 53 samples of Escherichia coli (61.0%), 7 of Candida spp. (8.0%), 6 of Salmonella spp. (6.9%), 5 of Morganella spp. (5.7%), 4 of Klebsiella spp. (4.6%), 3 of Providencia spp. (3.45%), 2 of Pseudomonas spp. and Staphylococcus spp. (2.3%) and 1 of Citrobacter spp., Edwarsiella tarda, Enterococcus spp., Moerella spp. and Proteus mirabilis were isolated. Of the anaerobic microbiota, 19 samples of Lactobacillus spp. (38%), 15 of Clostridium spp. (30%), 5 of Fusobacterium spp. (10%) and 4 of Peptoestreptococcus spp (8%) were isolated. From the proventriculus mucosa 15 samples of Candida spp. (51.7%), 6 of Lactobacillus spp. (20.7%), 5 of Aspergillus spp. (17,24%), 2 of Penicillium spp. (7%) and 1 of Staphylococcus spp. (3.45%) were identified. From the gizzard, 21 samples of Candida spp. (58.3%), 9 of Aspergillus spp. (25%), 5 of Lactobacillus spp. (13.9%) and 1 sample of Sthaphylococcus spp. (2.8%) were isolated.

A criação de avestruz (Struthio camelus) vem sendo implantada no país, despontando como uma alternativa lucrativa na pecuária brasileira, atraindo cada vez mais o interesse de novos criadores. A necessidade do conhecimento da microflora aeróbica e anaeróbica que compõem o trato gastrintestinal destas aves, além de contribuir para a própria sanidade destes animais, seria de identificar-se possíveis portadores de microrganismos patogênicos para o homem e os animais. O presente trabalho teve por objetivos identificar as espécies de microrganismos aeróbios e anaeróbios que compõem a microbiota gastrintestinal de animais necropsiados pela disciplina de Ornitopatologia do Departamento de Clínica, Cirurgia e Reprodução Animal. Do total de 30 aves necropsiadas, de ambos os sexos e com idade varindo entre 1 dia a 3 anos de idade foram isoladas 53 amostras de Escherichia coli (61,0%), 7 de Candida spp. (8,0%), 6 de Salmonella spp. (6,9%), 5 de Morganella spp. (5,7%), 4 de Klebisiella spp. (4,6%), 3 de Providencia spp. (3,45%), 2 de Pseudomonas spp. e Staphylococcus spp. (2,3%) e 1 de Citrobacter spp., Edwarsiella tarda, Enterococcus spp., Moerella spp. e Proteus mirabilis. Da microbiota anaeróbica, foram isolados 19 amostras de Lactobacillus sp. (38%), 15 de Clostridium spp. (30%), 5 de Fusobacterium spp. (10%) e 4 de Peptoestreptococcus spp. (8%). Da mucosa do próventrículo foram identificadas 15 amostras de Candida spp. (51,7%), 6 de Lactobacillus spp. (20,7%), 5 de Aspergillus spp. (17,24%), 2 de Penicillium spp. (7%) e 1 de Staphylococcus spp. (3,45%), enquanto que da moela foram isolados 21 amostras de Candida spp. (58,3%), 9 de Aspergillus spp. (25%), 5 de Lactobacillus spp. ( 13,9%) e 1 amostra de Sthaphylococcus spp. (2,8%).
DETERMINATION OF THE GASTROINTESTINAL MICROFLORA OF OSTRICHES (STRUTHIO CAMELUS) FROM THE NORTHWEST AREA OF THE SÃO PAULO STATE, BRAZIL, SUBMITTED TO NECROPSY
Keywords: Ostriches (Struthio camelus); aerobic; anaerobic; gastrointestinal microflora.; Avestruz (Struthio camelus); aeróbica; anaeróbica; microflora gastrintestinal.